PENGARUH PENGGUNAAN KARTU BANTU DENGAN RINGKASAN MATERI TERHADAP HASIL BELAJAR BIOLOGI (FPMIPA IKIP PGRI Bali, 2016)
Biology is an important lesson to learn at school. But sometimes there are problem that found in the action of learning biology. Some of those problem are the teacher uses a little variations in the learning process and there are many technical terms of biology. Assist cards with summary is a media that can used in learning process. The aim of this research is to determine the influence of using assist cards with summary toward students’s biology learning result in class X SMAK Thomas Aquino Tangeb Mengwi Academic Year 2015/2016. The type of this research was quasy experiment. Design of this research was Non-equivalent Posttest Only Control Group Design. The research population were all of the studenst in class X SMAK Thomas Aquino Tangeb Mengwi Academic year 2015/2016 which consist of 5 classes. This research used multi stage random sampling to got the research sample. Class X 1 as the control class and class X 3 as the experiment class. The data of students’s learning result have gotten by using essay test and analyzed by using t-test. Based on the analysis, obtained thitung = 2,49 and ttabel = 2,021 with the significance level 5%. It shows that thitung > ttabel (2,49 > 2,021) so H0 refused and H1 accepted. It can be conclude that there is the influence of using assist cards with summary toward students’s biology learning result in class X SMAK Thomas Aquino Tangeb Mengwi Academic Year 2015/2016.